2016
DOI: 10.1016/j.celrep.2016.09.088
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Role for miR-9 and Argonaute Proteins in Balancing Quiescent and Activated Neural Stem Cell States

Abstract: SummaryThroughout life, adult neural stem cells (NSCs) produce new neurons and glia that contribute to crucial brain functions. Quiescence is an essential protective feature of adult NSCs; however, the establishment and maintenance of this state remain poorly understood. We demonstrate that in the adult zebrafish pallium, the brain-enriched miR-9 is expressed exclusively in a subset of quiescent NSCs, highlighting a heterogeneity within these cells, and is necessary to maintain NSC quiescence. Strikingly, miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 64 publications
3
50
1
Order By: Relevance
“…These results suggest that Notch signaling mechanisms regulate RG activity in the optic tectum in both regenerative and physiological conditions, and are like those in the retina, but not in the telencephalon. Previous studies report that under physiological conditions, inhibition of Notch signaling by a γ‐secretase inhibitor induced ascl1a expression and then ~80% of RG to become proliferative in the telencephalon (about 15% of RG are proliferative in the adult telencephalon) (Chapouton et al, ; Katz et al, ) and that under regenerative conditions, up‐regulation of Notch signaling was induced and inhibition of Notch signaling suppressed RG proliferation and neuronal regeneration (Kishimoto et al, ). Thus, response of Notch signaling to stab injury seems to be opposite between telencephalon and optic tectum.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that Notch signaling mechanisms regulate RG activity in the optic tectum in both regenerative and physiological conditions, and are like those in the retina, but not in the telencephalon. Previous studies report that under physiological conditions, inhibition of Notch signaling by a γ‐secretase inhibitor induced ascl1a expression and then ~80% of RG to become proliferative in the telencephalon (about 15% of RG are proliferative in the adult telencephalon) (Chapouton et al, ; Katz et al, ) and that under regenerative conditions, up‐regulation of Notch signaling was induced and inhibition of Notch signaling suppressed RG proliferation and neuronal regeneration (Kishimoto et al, ). Thus, response of Notch signaling to stab injury seems to be opposite between telencephalon and optic tectum.…”
Section: Discussionmentioning
confidence: 99%
“…45). Very recently, it was shown that miR-9 potentiated Notch signaling to maintain quiescence in adult zebrafish NSCs 46 . In the context of this process, miR-9 is actively shuttled into the nucleus, a phenomenon mediated by binding of the miR-9-Ago complex to the shuttle protein TNRC6 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it was shown that miR-9 potentiated Notch signaling to maintain quiescence in adult zebrafish NSCs 46 . In the context of this process, miR-9 is actively shuttled into the nucleus, a phenomenon mediated by binding of the miR-9-Ago complex to the shuttle protein TNRC6 46 . The function of these nuclear Ago-miR-9 complexes stands in apparent contrast to the function of cytoplasmatic miR-9 in embryonic zebrafish NSCs, where miR-9 is expressed in cycling NSCs and serves to promote neuronal differentiation, an effect at least partially mediated by interference with Notch signaling 17 …”
Section: Introductionmentioning
confidence: 99%
“…Some levels of heterogeneity have also been observed molecularly, for instance, variable levels of the Zinc finger protein Fezf2 regulate Notch activity levels and quiescence of NSCs (Berberoglu et al, 2014) . Likewise, the expression of miR9 involved in keeping quiescence upstream of Notch signaling is found only in a subset of quiescent cells (Katz et al, 2016) several days after a division. In a recent study, a subpopulation of NSCs that expresses low levels of Elavl3 has been characterized as mostly non-dividing cells in transit towards neuronal differentiation (Lange et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Besides signals from the environment, cell-intrinsic modulations have been shown to impact on the proliferative activity, for instance the metabolic control of lipogenesis that can induce proliferation (Knobloch et al, 2013(Knobloch et al, , 2017 . Conversely, the expression of miR-9 (Katz et al, 2016) or the degradation of Ascl1 via the ubiquitin ligase Huwe1 are factors inducing quiescence. While a combination of signals received from the environment and intrinsic to the cells seem to influence proliferating activity, it remains to be precisely understood whether and how cells coordinate their activity with their neighbors.…”
Section: Introductionmentioning
confidence: 99%